2016
DOI: 10.25307/jssr.274319
|View full text |Cite
|
Sign up to set email alerts
|

Özel Yetenek Sinavlarina Gi̇ren Adaylarin Genel Öz Yeterli̇li̇k Düzeyleri̇ni̇n Bazi Deği̇şkenlere Göre İncelenmesi̇

Abstract: EXAMINATION OF THE GENERAL SELF-EFFICACY OF CANDIDATES WHO TOOK THE SPECIAL ABILITY EXAM ACCORDING TO SOME VARIABLES ABSTRACT Original ArticleThe purpose of this study was to examine according to some variables the general self-efficacy of the candidates who took the special ability exam of the Physical Education and Sports Department. This study population consisted of 1395 candidates, selected by random sampling, and 705 volunteers who were taking the special ability exam of the Erciyes University Physical E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Kabak (2019) stated in their study that there was no significant difference according to the age variable. In another study, Turan et al (2016), on the other hand, did not observe a significant difference in their study in which they examined the general self-efficacy scores of the participants according to their age. Tatar (2017) examined the relationship between the life satisfaction of physically disabled people who do sports and those who do not and stated that doing sports has no effect on the feeling of life satisfaction in individuals between the ages of 15-19.…”
Section: Discussionmentioning
confidence: 86%
“…Kabak (2019) stated in their study that there was no significant difference according to the age variable. In another study, Turan et al (2016), on the other hand, did not observe a significant difference in their study in which they examined the general self-efficacy scores of the participants according to their age. Tatar (2017) examined the relationship between the life satisfaction of physically disabled people who do sports and those who do not and stated that doing sports has no effect on the feeling of life satisfaction in individuals between the ages of 15-19.…”
Section: Discussionmentioning
confidence: 86%
“…As a result, less anxiety, a healthier and stronger mind and mood occur (Doğan, 2017;Gül and Çeliköz, 2018). According to literature, studies on self efficacy (Turan et al, 2016;Izgar and Dilmaç, 2008;Caba and Pekel, 2017;Saracaloğlu et al, 2017;Güler, 2022;Akıncı, 2020) and patience of various sample groups were found. (Bettinger and Slonim., 2007;Karakaş, 2016;Gül and Çeliköz, 2018;Ermiş and İmamoğlu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of universities, it is very important to include personal development activities in curriculums to improve their general self-efficacy and professional qualifications (Turan et al 2016). It is necessary to contribute to the development of personality that includes motivation.…”
Section: Introductionmentioning
confidence: 99%